INVESTIGATING ADVANCED LEARNERS’ USE OF AFFECTIVE STRATEGIES FOR DEALING WITH TEST ANXI-ETY - Mystkowska-Wiertelak, Anna (Neofilolog, 2018)
Language anxiety has been researched for many decades now and its significance for attainment cannot be questioned. In numerous research accounts anxiety related to learning a foreign/second language comes in different guises, as speaking anxiety, or communication apprehension, fear of negative evaluation, and finally, test anxiety. In fact, developing linguistic competence in the formal setting is inherently fraught with the need to have one’s skill and knowledge verified in the form of informal and formal, low- or high-stakes tests and examinations. Alleviating the negative consequences of anxiety seems imperative for effective learning, which in the opinion of the present author, will not be possible without gaining a deeper insight into the ways in which learners deal with negative feelings evoked by language study or use. Hence, an attempt has been made to explore the range of strategies employed by a specific group of learners – English majors in their final year of study – to cope with a stressful situation such as a regularly-scheduled achievement test in one of the components of the practical English course. What distinguishes this group of learners is their level of proficiency, which is C1 or nearing C2, but most importantly of all, their long-term experience of dealing with stress that has extended throughout formal education including the duration of MA studies in English Philology. Data collected by means of immediate reports and questionnaires revealed that the participants employed quite a limited scope of stress-reducing strategies and that there were characteristic trends, the analysis of which could serve as a point of departure for offering effective strategy instruction capable of relieving the consequences of negative affective states.